Flower-like ZnO Nanostructures as Gas Sensor. (2019) - Tiwary, P.; Chakrabarty, N.; Chakraborty, A.K.; Mahapatra, R.
Abstract: In this work, we report the synthesis of ZnO nanostructures using a simple solvothermal method and then investigate their use in sensing of ammonia (NH3 ) and some volatile organic compounds (VOC) such as ethanol and methanol. Electron microscopic analysis shows that the synthesized nanorods are arranged in a flower-like array while UV-Vis absorption spectroscopy shows a peak at 380 nm confirming presence of ZnO. Resistances measured across a thin film of the ZnO nanoflowers show sharp decrease when exposed to ammonia and the VOCs with highest sensitivity recorded for ethanol suggesting its potential use in sensing of these gases.